2018
DOI: 10.3390/su10072134
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Public Procurement Policies on Promoting Scientific and Technological Innovation in China: Comparisons with the U.S., the UK, Japan, Germany, France, and South Korea

Abstract: In many countries, sustainable public procurement is a powerful tool to reflect on national strategic intentions and promote scientific and technological innovation. Based on the perspective of an institutional structure, we filtered out the core policies. Using policy bibliometrics, we analyzed Chinese public procurement policies on promoting scientific and technological innovation, revealed policy-making characteristics, and concluded that the Ministry of Finance should appropriately decentralize the policy-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…This method has been applied in a few previous studies related to policy analysis, and its effectiveness has been well confirmed (e.g. Huang et al, 2018a;Noyons, 2001;Wang et al, 2018). Bibliometric analysis can be utilized to capture the historical dynamics of policy themes as well as the evolving collaborative relationships of policymaking organizations (Huang et al, 2015;Provan & Kenis, 2007;Saidi et al, 2017;Yao & Zhang, 2018;Zhang et al, 2018a).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This method has been applied in a few previous studies related to policy analysis, and its effectiveness has been well confirmed (e.g. Huang et al, 2018a;Noyons, 2001;Wang et al, 2018). Bibliometric analysis can be utilized to capture the historical dynamics of policy themes as well as the evolving collaborative relationships of policymaking organizations (Huang et al, 2015;Provan & Kenis, 2007;Saidi et al, 2017;Yao & Zhang, 2018;Zhang et al, 2018a).…”
Section: Methodsmentioning
confidence: 99%
“…After collecting the data, we converted the PBP documents into simple text format, then mined the texts for keywords to use in the bibliometric analysis (Huang et al, 2015;Wang et al, 2018). Keywords extraction can facilitate an understanding of the implications of PBPs because the keywords in a PBP document reflect the most important PBP topics (Huang et al, 2015;Wang et al, 2018). Frequency-inverse document frequency, a widely used text mining method, was used to perform the keyword extraction (Kim et al, 2016).…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Entrepreneurship is one of the important factors to promote economic development, and innovation is also the source of economic development in China. Both are indispensable in the process of economic and social development in China (Huang et al, 2018;Wang et al, 2018). However, there are very few successful entrepreneurs, which makes people wonder why some entrepreneurs may succeed.…”
Section: Introductionmentioning
confidence: 99%
“…Public sector procurement is increasingly seen as an important instrument for inducing innovation in the private sector (Lenderink et al 2019). Sustainable public procurement is a powerful tool to reflect on national strategic intentions and promote scientific and technological innovation (Hu et al 2018;Wang et al 2018aWang et al , 2018bJobidon et al 2018;Ivashova and Ivashov 2019, p. 327).…”
Section: Introductionmentioning
confidence: 99%